(untitled) (Research, Society and Development, 2022)
The disorganized growth of urban centers, added to the lack of public policies and targeted investments, cause irreparable damage to the environment as a whole and to the health of populations due to failures in the basic sanitation system. The objective of this work was to evaluate the impacts caused by the discharge of untreated effluents into the Rio Negro river; carry out microbiological analyzes of water samples from various points on the edge of Manaus, as well as streams (small tributaries of the Rio Negro), in order to assess the health of these water bodies, and the progress of their pollution today, comparing the results obtained within the limits permitted by current legislation; to analyze the possibility of dumping untreated wastewater directly into the Rio Negro river, mainly from the use of the subfluvial outfall, from the perspective of the aforementioned having a supposed capacity for self-purification. Another goal of this study is to propose the updating of the Municipal Basic Sanitation Plan of the city of Manaus, mainly with regard to the establishment of a maximum period to reach a satisfactory percentage in the population’s access to sewage collection and treatment in the municipal network. For that, water samples were collected from five points of the city coast and microbiological characterization analyzes were carried out. It was possible to infer from the results that the pollution in the creeks on the edge of Manaus is evident, considering that in all five points evaluated the presence of microorganisms harmful to human health was found, largely due to the receipt of disorderly effluent discharge.